The role of first trimester uterine artery pulsatility index as a predictor of hypertensive disorders of pregnancy in the department of obstetrics and gynaecology, Sawai Man Singh Medical College, Jaipur - Shivrayan, Suman; Vyas, Jyotsna; Kuntal, Chelsae; Jakhar, Balveer; Poonia, Vikas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: This study was conducted to assess the relationship between mean uterine artery pulsatility index at 11+0 to 13+6 weeks and the development of hypertensive disorders of pregnancy. Methods: This prospective study was carried out on 320 pregnant women. In all subjects mean uterine artery PI was calculated at 11+0 to 13+6 weeks and association of value of uterine artery PI and development of hypertensive disorder of pregnancy were compared by receiver operative curve analysis. Results: The ROC curve analysis shows that at the cut-off value of 1.62, overall sensitivity, specificity, positive predictive value, and negative predictive value of PI for prediction of hypertensive disorder of pregnancy in our study was 82.1% (95% CI- 63.1-93.9%), 57.4% (95% CI- 51.5-63.2%), 15.7% (95% CI- 13.1-18.9%) and 97.1% (95% CI-93.7-98.7%) respectively. When we evaluate 11+0 to 13+6 weeks UtA PI value with hypertensive disorders of pregnancy and early-onset hypertensive disorders of pregnancy by AUC curve, we found that the area under curve was 0.73 (95% CI 0.64-0.81) and 0.78 (95% CI 0.69-0.86) respectively. Conclusions: Uterine artery pulsatility index at 11+0 to 13+6 weeks is significantly higher in women who develop hypertensive disorder in pregnancy. Our study also shows that 11±0 to13±6 weeks uterine artery pulsatility index was a more significant predictor of early onset pre-eclampsia. It is a simple, non-invasive, reliable test which can be performed as an adjunct to routine ultrasound examination to predict hypertensive disorders.